The Relationship between Understanding and Parental Participation in Participating in Parenting Programs in PAUD Aisyiyah 14 Kota Padang - Dela Yolanda; Resti Dwi Yulia (Universitas Negeri Padang, 2020)
Many parents are not actively participating in the parenting program. This can be seen by 35 parents of children in PAUD Aisyiyah 14 Ampang, Padang City, only 15 parents (42%) who participated in parenting by participating and being involved and actively participating in parenting activities by attending parenting programs regularly every month. Meanwhile, there were 20 parents (58%) who did not participate in the parenting program themselves. As for this data, researchers obtained through interviews with managers at PAUD Aisyiyah 14 Ampang, Padang City, where parenting program activities take place every Tuesday, the 2nd week of each month. Based on the research results above, it can be concluded that parents' understanding of parenting and their participation in participating in parenting activities has a significant relationship. This means that if the understanding of parenting is high, the higher participation in participating in activities, and vice versa. In organizing an activity there are things that must be understood by the organizer of the program or activity, with the aim that the activity can run smoothly and can achieve the objectives as expected. In increasing parental participation in carrying out parenting activities, it is not easy. For this reason, the role of parents is very influential in maximizing parental participation rates in the implementation of parenting activities.Keywords: Understanding, Participation, Early Childhood Education